Enhancing decision knowledge by developing a quantitative framework for holistic exploratory acquisition policy analysis. Issue 5 (28th June 2022) - Kwon, Kybeom; Kim, Heungseob; Min, Seungin; Kim, Cheonyoung; Jee, Cheolkyu; Seol, Hyeonju
Abstract: An acquisition policy's diverse stakeholders may have heterogeneous needs. Furthermore, stakeholders may be unsure of their preferences due to a highly qualitative analysis of alternatives in the early stages of the acquisition policy development process. Lacking system knowledge and evidence, stakeholders may push back policy priorities or delay decisions. In such cases, it is necessary to increase stakeholders' knowledge about the acquisition policy options' impacts. This study proposes a systematic and quantitative framework development process and outlines a holistic exploratory policy analysis. Stakeholders' needs are systematically identified and measurement areas and elements are derived from those needs. Evaluation methods are then created through a sensible quantification process to measure the impact of introducing each alternative. The framework provides information on the effects of various policy options, an analysis of each alternative's most crucial policy option, and other valuable analysis results. Finally, we present a case study to illustrate the development process and application of the framework when introducing a new military training system such as Live, Virtual, and Constructive synthetic training systems.